Cephalometric evaluation of natural head position in Lingayat population of Karnataka - Inderpreet Singh; K Kiran Kumar; Pradeep Raj; R Haranadh Babu; Narendra Pithani; Altaf H Thekiya (Journal of Pharmacy and Bioallied Sciences, 2019)
Aims and Objectives: To ascertain norms in cephalometry for 11- to 13-year-old Lingayat children in natural head position (NHP). Materials and Methods: Lateral cephalograms of children were obtained by using fluid level device. We determined the variance in Frankfort horizontal plane (FHP) inclination to extracranial horizontal in NHP. The GFNx01Power, version 20 for Windows was used for analysis. Results: Reduced facial convexity was observed when the analysis was carried out in relation to true horizontal with significant difference of “t” value of 3.05 and percentage difference of 1.1 (P < 0.01) and for girls “t” value of 9.69 and percentage difference of 2.5 (P < 0.001). The highest correlation coefficient for Lingayat boys (r = 0.77) was seen between palatal plane and occlusal plane. We found least correlation coefficient among FHP and Sella–nasion plane (SNP). The coefficient was r = 0.62 and correlation coefficient of r = 0.70 was between FHP and determination coefficient r2 = 0.38 or 38%. For girls, highest correlation coefficient of r = 0.70 was seen among FHP and palatal plane. Conclusion: Conventional study of craniofacial forms of Lingayat children showed the average skeletal pattern as Class II with retrognathic mandible in comparison to Caucasians. However, when seen in NHP by new method of analysis based on the true horizontal, the skeletal model was Class III in comparison to Caucasians.